Students' Performances in Computer Programming of Higher Education for Sustainable Development: The Effects of a Peer-Evaluation System - Hsiao, Tsung-Chih; Chuang, Ya-Hsueh; Chen, Tzer-Long; Chang, Chien-Yun; Chen, Chih-Cheng (Frontiers in Psychology, 2022)
Modern education attaches great importance to interdisciplinary skills, among which computational thinking is a core element, and heralds a new era. IT application has shaped education in the 21st century. Computational thinking has provided further impetus for building an all-encompassing social network and fostering a DIY culture enabled by digital technologies. One empirical study used four apps to test children's development in computational thinking and fluency. The article will help students overcome their fears of coding. Peer reviews provide students with an opportunity to learn from each other and become more motivated. These reviews also serve as feedback for teachers to evaluate students' performance. Experimental design is used in this study, and a peer review system is implemented. Freshmen attending a programming class in a university are used as samples. At the class, students write computer programs with f-Chart, which provides a graphical user interface for students to learn programming logic and design. Zuvio, a cloud-based interactive response system, is used to conduct the peer reviews. The data of this study are analyzed through R. The results show not only an improvement in students' learning performance but also a gap between students' peer review scores and teachers' evaluation scores. Learning feedback and evaluation is crucial to transform education between students and teachers into a sustainable cycle system.